Edukasi Gizi terhadap Pengetahuan dan Kebiasaan Jajan pada Siswa SMP Negeri 35 Makassar - Asmarudin Pakhri; Chaerunnimah Chaerunnimah; Rahmiyati R (Media Gizi Pangan, 2018)
One effort to increase knowledge is to educate health about nutrition especially. Nutrition education is essentially an activity to deliver a health message to a community or group in the hope of influencing the behavior of the target. The habit of snacking is part of the action-shaped behavior that becomes a pattern of the behavior of a person or group that tends to be difficult to change. This study aims to determine the effect of nutritional education on knowledge and habits of jajan at students of SMP Negeri 35 Makassar. The type of research is pre experimental study with one group pre-test and post-test design. The location of the research was conducted at SMP Negeri 35 Makassar. Samples are students of class VIII of 100 students obtained by simple random sampling. The study was conducted on April 8 - April 22, 2017. The results are presented in tabular and narrative form. Based on the results of research conducted at SMP Negeri 35 Makassar shows that the knowledge of students before given less than 58% of good nutrition education and good (42%) using Wilcoxon statistical test obtained value (p=0,000) which means there is influence of education Nutrition to knowledge in students. In the habit of snack before given nutrition education that is as much (63%) and good as much (37%), using Wilcoxon statistic test obtained value (p=0,372) which means there is no effect of nutritional education to snack habits on students. Nutrition education with reverse sheet media shows there is an influence on knowledge but there is no effect on the snack habits. Keywords: Knowledge, Nutrition Education, Pocket Habits